Fatigue Life Assessment of Deck Barge Construction Using Numerical Simulation Methods - Alamsyah Alamsyah; Irvan Setiawan; Amalia Ika Wulandari; Rodlian Jamal Ikhwani; Suardi Suardi (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Barges are used as the main means of transporting heavy goods such as nickel, wood, coal and other materials that are placed on the main deck and have implications for stress values ​​and construction fatigue life. This study uses a numerical simulation method with the help of ANSYS software. The load simulations given to the main deck construction of the barge are 50% load, 75% load, and 100% load (full load). The results of the numerical simulation detected that the largest stress occurred when the 100% load condition was 190.7 MPa. The stress with 75% load is 160.21 MPa and the stress for 50% load is 129.73 MPa. The fatigue life at 100% load is 10.66 years with a stress cycle of 170000 times, 75% load is 13.49 years with a stress cycle of 300000, and a 50% load is 21.16 years with the a stress cycle of 700000. -